Thermal conductivity measurement of organic solvents incorporated with silver nanoparticle using photothermal techniques. Issue 1 (17th February 2015) - Basheer, N Shemeena; Kumar, B Rajesh; Kurian, Achamma; George, Sajan D
Abstract: The present paper summarizes our recent work on heat transfer of nanofluid in different organic solvents determined using photothermal techniques. UV- Visible absorption spectrum shows an intense surface plasmon absorption peak at 427 nm. TEM indicates the presence of well dispersed silver nanoparticles having spherical morphology with particle size ranging from 10 to13 nm. The experimental results show that thermal conductivity of organic solvents increases with the incorporation of silver nanoparticles.